2007
DOI: 10.1037/cjep2007006
|View full text |Cite
|
Sign up to set email alerts
|

Categorization of environmental sounds.

Abstract: This paper investigates the way in which people categorize environmental sounds in their everyday lives. Previous research has shown that isolated environmental sounds are categorized on the basis of high-level semantic features when the sounds can be attributed to specific sound sources. However, in the presence of numerous sound sources, as occur in most real-world situations, the process of source identification is often hindered. In the present study, a free categorization task with open-ended verbal descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(51 citation statements)
references
References 25 publications
3
47
0
1
Order By: Relevance
“…The interpretation of the third perceptual dimension is less clear, but it appears to relate to the presence of people with non-diegetic music and effects at one extreme of the dimension, and dialogue and crowd reactions appearing at the other extreme. This is consistent with findings in soundscapes research [19] and research into the perception of complex audiovisual scenes [22].…”
Section: Interpretation Of Perceptual Dimensionssupporting
confidence: 79%
See 1 more Smart Citation
“…The interpretation of the third perceptual dimension is less clear, but it appears to relate to the presence of people with non-diegetic music and effects at one extreme of the dimension, and dialogue and crowd reactions appearing at the other extreme. This is consistent with findings in soundscapes research [19] and research into the perception of complex audiovisual scenes [22].…”
Section: Interpretation Of Perceptual Dimensionssupporting
confidence: 79%
“…A study into auditory categories for environmental sounds in complex auditory scenes revealed two main categories relating to the presence or absence of human activity [19], and common categories for auditory events in soundscapes include "natural," "human," and "mechanical" [see Payne et al…”
Section: Papers Categorization Of Broadcast Audio Objects In Complex mentioning
confidence: 99%
“…Further to this, the event also overrided context and location [Gygi et al 2007], and overrided any shared physical properties when participants focused on the mental image generated by each stimulus [Scavone et al 2002]. When sounds were more complex like sequences of environmental sounds, the categorization was more closely related to global judgment like the absence or presence of human activity [Guastavino 2007]. The primary category was composed of traffic noise, and the latter one of subcategories of sounds corresponding to interactions with the environment through socialized activities.…”
Section: Introductionmentioning
confidence: 99%
“…In general, these more cognitively-oriented studies seem to indicate that environmental sounds are remembered differently and less well than speech. Whereas speech, and to a lesser extent music, can be abstracted away from the auditory stimulus to a generative symbolic system, retaining largely the semantic content (perhaps because for both classes of sounds there exist a standardized notation system), it seems that memory for environmental sounds is grounded in the nature of the events that produced the sounds [30,43,44], which enables faster learning of auditory icons that refer directly to meaningful events [45].…”
Section: Cognitive Processing Of Environmental Soundsmentioning
confidence: 99%